You say you want a revolution? : radical idealism and its tragic consequences - Chirot, Daniel 1942- (Princeton University Press, 2020)
"This book poses the question of why revolutions--from the French Revolution through the Russian and more recent revolutions--tend to produce tragic outcomes. As the author puts it: 'I have become intrigued with the idea of writing a short book on why so many revolutions turn into bloody catastrophes. Though a huge amount has obviously been written about revolutions, I think a good short review of why they so often disappoint so badly could find a good audience. Of course the planned book would not please those with different views. I want to insist on the contingent nature of what happened rather than seeing revolutions in a Marxist way as necessary and inevitable steps toward world historical progress. I also believe that key individuals make a big difference, so the purely structural analyses that predominate in sociology and political science lack an important element. Then, too, the age of revolutions is far from over, and while I don't really think that history repeats itself, there are recurrent patterns to watch out for.' Chirot proceeds by exploring the combination of extremism and incompetence that characterize most revolutionary movements, the effects of counter-revolutionary forces in complications post-revolutionary regimes, the often tyrannical application of idealistic norms on societies experiencing revolutionary change, and the corruption and oppression that often characterize post-revolutionary regimes. He plans to end the book with a chapter on what can be learned from his study with respect to future revolutionary movement"--